Cloning of the Membrane-Bound Aldehyde Dehydrogenase Gene of Acetobacter polyoxogenes and Improvement of Acetic Acid Production by Use of the Cloned Gene - Fukaya, Masahiro (1989)
A genomic clone bank of Acetobacter polyoxogenes NBI1028 constructed in Escherichia coli by use of the expression vector pUC18 was screened with antibody raised against membrane-bound aldehyde dehydrogenase (ALDH; 75 kilodaltons [kDa]) from A. polyoxogenes NBI1028. A clone that synthesized a 41-kDa protein cross-reactive with anti-ALDH antibody was isolated. For cloning of the full-length ALDH structural gene, a cosmid gene bank was screened by Southern blot hybridization with the cloned DNA as a probe, and subcloning from the positive cosmid clone was performed with shuttle vector pMV24. Plasmid pAL25, containing the full-length ALDH structural gene, was isolated and expressed in both E. coli and Acetobacter aceti to produce a fused protein (78 kDa) with a short NH(2)-terminal β-galactosidase peptide. pAL25 conferred ALDH production on a mutant of A. aceti lacking the enzyme activity. Transformation of A. aceti subsp. xylinum NBI2099 with pAL25 caused 2- and 1.4-fold increases in the production rate and in the maximum concentration of acetic acid in submerged fermentation, respectively.